Projective Identification in Counselling: Theoretical and Therapeutic Considerations - Clark, Arthur J. (Canadian Journal of Counselling and Psychotherapy, 2007)
Projective identification is one of the most compelling and misunderstood contributions of psychoanalytic theory to the practice of counselling and psychotherapy. Projective identification has direct relevancy in the counselling experience as a client defense mechanism that is simultaneously subtle, complex, and challenging. A three-phase sequence of the manifestation of projective identification is conceptualized that induces the counsellor to assume projected qualities of the client. Projective identification is distinguished from related concepts, including projection, identification, and transference. Therapeutic strategies for recognizing and effectively processing the defense mechanism in individual and group counselling are presented, including a case illustration.